Clinico - Pathological Study of A Herbo-Mineral Compound And Guduchi Satwa On Sickle Cell Anaemia w.s.r. To Sannipatika Pandu - Majhi, Dusmanta Kumar; Nayak, Utkalini; Panda, Pradip Kumar; Rajesh, Apratim Sai (International Research Journal of Ayurveda & Yoga, 2021)
Introduction: Sannipatika Panduroga, described in Ayurveda classics resembles to the clinical features of Sickle cell Anaemia (SCA). Sickle cell Anaemia results from substitution of a single Amino Acid; Glutamic Acid in place of Valine at 6th position of the β globin polypeptide chain, which produce homozygous (HbSS) and heterozygous (HbAS), mainly two varieties of Sickle cell Disease (SCD) Materials and methods: A clinical study on 30 Sannipatika pandu roga patients, (15 patients each in Group-A and Group-B) were registered from OPD and IPD of Govt. Ayurvedic College and Hospital, Balangir, Odisha. The patients presented with the Subjective Parameters of Panduta (Pallor of the skin), Durvalata (Weakness), Sadana (Fatigue), Angamarda (Body ache), Jwara (Fever), Swasa (Dyspnoea), Aruchi (Anorexia), Gourava (Heaviness), Chhardi (Vomiting), Mala-Mutra and Netraswetata (pale colouration of urine, stool and eye) and Objective parameters as CBC, ESR Sickling test (24 hours method) and Hb Electrophoresis were selected for clinical study. Group-A patients were treated with Herbo-Mineral Compound (500mg) and Group-B patients with Guduchi Satwa (500 mg) twice daily in empty stomach with honey orally for 30 days respectively. The patients were assessed at 10 days interval up to 30 days in order to find the efficacy of both the trial drugs. The subjective and objective parameters were analysed statistically by Wilcoxon-W test and p-value. Observation and result: There were 65.15% and 40.85% of improvement in signs and symptoms and 25% & 17.65% of increase in the level of Hb gm% in the patients of Group-A and Group-B were observed in this study respectively. The Statistically significant (P<0.05) result was revealed in both Group-A and Group-B but improvement was noticed more in Group-A. Conclusion: -The overall study revealed that the trial on Herbo-Mineral Compound i.e., Group-A showed more efficacy than Guduchi satwa i.e, Group-B. The composition of Herbo-Mineral Compound helped more to develop the body immunity as well as maintain the haematological parameters rather than single Guduchi satwa. No adverse effects was noticed during clinical trial in both groups.